Songs and Poems of the Farmers’ Protests - Compilation (Sikh Research Journal, 2021)
The following compilation consists of the lyrics of two songs and the text of three poems. The songs are in Punjabi, and have been transliterated here, as well as translated. No doubt, the transliterations and translations can be improved, but are hopefully good enough to convey meanings adequately. Both songs have video versions, and the music and video are important parts of the experience and impact of each song, of course.